Guideline for Developing Digital Citizenship of Teachers Under Nongkhai Primary Education Service Area Office 2 - Limtrkul, Nopporn; Sonsupee, Sittichai (Journal of Graduate MCU KhonKaen Campus, 2024)
The objectives of this research article are 1. To study the present and desirable conditions of digital citizenship among teachers. under the Office of Nong Khai Primary Educational Service Area Office 2 and 2) Study the digital citizenship development guidelines for teachers under the Office of Nong Khai Primary Educational Service Area Office 2. This research was descriptive research. The sample group consisted of 279 school administrators and teachers. Phase 1 was a quantitative data collection using a questionnaire. Data were analyzed by statistical values, frequency, percentage, and standard deviation. and prioritize the necessary needs. Phase 2: qualitative data collection by structured interview forms The target group of 5 people was derived from the specific selection. To find ways to develop teachers’ digital citizenship. Analyze the content and present it in a descriptive way. 1. The study found that the Average current condition level was at a high level The aspect with the highest average was digital security. and the desirable condition was at the highest level. The area with the highest average was digital communications. The need for digital citizenship development guidelines Overall, it was found that digital communication was the area with the highest need. And the area with the lowest need is digital access. 2. The result of the Guidelines for Developing Digital Citizenship of Teachers under Nong Khai Primary Educational Service Area Office 2 was found that 1) teachers with self-development plans Are able to work and have skills in using technology to assist in teaching and learning management. 2) Promote effective digital communication. 3) Parent agencies must allocate sufficient budgets that are suitable for the needs of the Internet signal to meet the needs of teachers to be able to use it. 4) Promote knowledge related to intellectual property. Teacher’s Digital Law Avoid copyright infringement. 5) Promote the use of digital information with caution. Be up to date with the dangers arising from digital use.